Bipolar disorders and retinal electrophysiological markers (BiMAR): Study protocol for a comparison of electroretinogram measurements between subjects with bipolar disorder and a healthy control group - Gross, Grégory; Tursini, Katelyne; Albuisson, Eliane; Angioi-Duprez, Karine; Conart, Jean-Baptiste; Louis Dorr, Valérie; Schwan, Raymund; Schwitzer, Thomas (Frontiers in Psychiatry, 2022)
Background: Bipolar disorders (BD) is a common, chronic and disabling psychiatric condition. In addition to being characterized by significant clinical heterogeneity, notable disturbances of sleep and cognitive function are frequently observed in all phases of the disease. Currently, there is no readily available biomarker in current clinical practice to help diagnose or predict the disease course. Thus, identification of biomarkers in BD is today a major challenge. In this context, the study of electrophysiological biomarkers based on electroretinogram (ERG) measurements in BD seems highly promising. The BiMAR study aims to compare electrophysiological data measured with ERG between a group of euthymic patients with BD and a group of healthy control subjects. Secondarily, we will also describe the existing potential relationship between clinical, sleep and neuropsychological phenotypes of patients and electrophysiological data. Methods: The BiMAR study is a comparative and monocentric study carried out at the Expert Center for BD in Nancy, France. In total, 70 euthymic adult patients with BD and 70 healthy control subjects will be recruited. Electrophysiological recordings with ERG and electroencephalogram (EEG) will be performed with a virtual reality headset after a standardized clinical evaluation to all participants. Then, an actigraphic monitoring of 21 consecutive days will be carried out. At the end of this period a neuropsychological evaluation will be performed during a second visit. The primary outcome will be electrophysiological measurements with ERG flash and pattern. Secondary outcomes will be EEG data, sleep settings, clinical and neuropsychological assessments. For patients only, a complementary ancillary study, carried out at the University Hospital of Nancy, will be proposed to assess the retinal structure and microvascularization using Optical Coherence Tomography. Recruitment started in January 2022 and will continue until the end of July 2023. Discussion: The BiMAR study will contribute to identifying candidate ERG electrophysiological markers for helping the diagnosis of BD and identify subgroups of patients with different clinical profiles. Eventually, this would allow earlier diagnosis and personalized therapeutic interventions. Clinical Trial Registration: The study is registered at Clinicaltrials.gov, NCT05161546, on 17 December 2021 (https://clinicaltrials.gov/ct2/show/NCT05161546).